PENGEMBANGAN MEDIA KOMIK ELEKTRONIK BERBASIS POTENSI LAUT BENGKULU UNTUK MENINGKATKAN LITERASI KEMARITIMAN SISWA SD - Muktadir, Abdul; Gumono; Atika Susanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop an electronic comic-based learning media utilizing the marine potential of Bengkulu, designed to effectively improve maritime literacy among elementary school students. The research uses the Research and Development (R&D) method with the Borg and Gall model. The study subjects include material experts, presentation experts, teachers, and students. The validation results show that the electronic comic media is considered "very valid" by both the material and presentation experts. User feedback from teachers and students also indicates that the media is "very feasible." Operational testing of the product was carried out through two learning cycles. In cycle I, the average maritime literacy score of students reached 66.33%, which significantly increased to 84.50% in cycle II. Thus, the electronic comic media based on the marine potential of Bengkulu is proven to be effective in enhancing maritime literacy among elementary school students. This media not only captures students' interest but is also relevant to local potential, making it a promising alternative learning medium based on local wisdom.